Immunotherapy Associated Vaginal Mucositis [31H]. (May 2020) - Patel, Jharna M.; Enich, Michael; Girda, Eugenia
Abstract : INTRODUCTION: Immune checkpoint inhibitors (ICPi), has revolutionized our approach to treating solid tumors, including gynecologic malignancies. Compared to standard chemotherapy, the adverse events associated with immunotherapies, are often mild and localized. While a rash is most commonly reported side effect of ICPi therapy, there have been few cases of mucositis caused by ICPi therapy, and no documented case of an ICPi therapy causing vaginal mucositis. METHODS: This is a presentation of a 67-year-old woman with a history of stage I metastatic uterine serous carcinoma who was initially treated with a hysterectomy, bilateral salpingo-oophorectomy, and lymphadenectomy. The patient had reoccurrence despite adjuvant radiation and chemotherapy and was enrolled in a phase 2 clinical trial with Cabozantinib and Nivolumab. Nine days after administration of IV Nivolumab during the second cycle, she reported onset of severe, non-radiating perineal pain. Pelvic examination revealed multiple, deep, erythematous ulcerations and necrosis around the periurethral area, consistent with grade 3 mucositis. The treatment was discontinued and she was started on prednisone therapy. Re-examination in 1 month showed decreased fibrinous material indicating that mucositis had improved. CONCLUSION: As immunotherapy is becoming more widely used in gynecologic malignancies, providers need to be aware of rare complications associated with these therapies. Such toxicities should be correctly identified and treated appropriately and expediently. Most patients will continue to benefit from administered immunotherapy and can be restarted once the toxicities are alleviated. To our knowledge, this is a first reported case of vaginal mucositis associated with Nivolumab therapy in a patient with gynecologic malignancy.